2020
DOI: 10.3390/antibiotics9040163
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing Antibiotics without a Prescription for Acute Cough Associated with Common Cold at Community Pharmacies in Shenyang, Northeastern China: A Cross-Sectional Study

Abstract: The inappropriate use of antibiotics is a major health issue in China. We aimed to assess nonprescription antibiotic dispensing and assess pharmacy service practice at community pharmacies in Shenyang, northeastern China, and to compare these practices between pediatric and adult cases. A cross-sectional study was performed from March to May 2018 using the standardized client method. Two different simulated scenarios were presented at pharmacies, namely, pediatric and adult acute cough associated with a common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
3
30
2
Order By: Relevance
“…A recent study found that the attitude of pharmacists regarding antimicrobial stewardship programs (ASPs) was positive. However, certain gaps in knowledge about some aspects of antimicrobials and participation in ASPs were highlighted coupled with a poor quality of pharmacy services [17,21,22]. No study has been undertaken to investigate the view of pharmacy staff toward ASPs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that the attitude of pharmacists regarding antimicrobial stewardship programs (ASPs) was positive. However, certain gaps in knowledge about some aspects of antimicrobials and participation in ASPs were highlighted coupled with a poor quality of pharmacy services [17,21,22]. No study has been undertaken to investigate the view of pharmacy staff toward ASPs.…”
Section: Introductionmentioning
confidence: 99%
“…The inappropriate use of antimicrobial drugs has become one of the main causes of increased AMDR worldwide [2]. Therefore, current strategies to combat AMDR are primarily focused on antimicrobial stewardship [3][4][5]. Moreover, according to the One Health perspective, AMDR can occur for different reasons, including human, animal or environmental factors [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, antibiotics were dispensed at the recommendation of the drugstore staff [11], [40], [43]. Conversely, in many simulated studies, antibiotics were mostly sold or dispensed by customer demand rather on the advice and recommendation of the attending staff [9], [44], [45]. Prescriptions were requested from the SCs in only 16.8% cases which indicates that strict implementation of the drug rules is required at the drugstores.…”
Section: Discussionmentioning
confidence: 99%